2021
DOI: 10.3389/fcell.2021.671857
|View full text |Cite
|
Sign up to set email alerts
|

Lnc-GD2H Promotes Proliferation by Forming a Feedback Loop With c-Myc and Enhances Differentiation Through Interacting With NACA to Upregulate Myog in C2C12 Myoblasts

Abstract: In the present study, the roles of a novel long non-coding RNA (lncRNA), lnc-GD2H, in promoting C2C12 myoblast proliferation and differentiation and muscle regeneration were investigated by quantitative polymerase chain reaction, western blotting, Cell Counting Kit-8, 5-ethynyl-2′-deoxyuridine (EdU), immunofluorescence staining, luciferase reporter, mass spectrometry, pulldown, chromatin immunoprecipitation, RNA immunoprecipitation assay, wound healing assays, and cardiotoxin (CTX)-induced muscle injury assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that MyoG and MyoD are both myogenic regulatory factors (MRFs), which play important roles in myoblast differentiation and fusion and can be used as mouse C2C12 myoblast differentiation marker genes ( Zhang et al, 2018 ; Chen et al, 2021b ). In chickens and mice, MyHC is highly expressed during myogenic differentiation and myotube formation and is also a differentiation marker gene in myogenesis ( Chen et al, 2019b ; Xu et al, 2019 ; Sakai et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that MyoG and MyoD are both myogenic regulatory factors (MRFs), which play important roles in myoblast differentiation and fusion and can be used as mouse C2C12 myoblast differentiation marker genes ( Zhang et al, 2018 ; Chen et al, 2021b ). In chickens and mice, MyHC is highly expressed during myogenic differentiation and myotube formation and is also a differentiation marker gene in myogenesis ( Chen et al, 2019b ; Xu et al, 2019 ; Sakai et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these factors, MyoG plays a crucial role in the growth, development and regeneration of skeletal muscle [50,51]. Additionally, Mef2c is a member of the myocyte enhancer factor 2 (Mef2) family, which involves in regulating the expression of muscle regulatory factors and skeletal muscle-specific transcription of these factors [52].…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA, which is characterized by a length exceeding a certain value, has emerged as crucial a regulator of gene function and expression levels in this context [25][26][27][28]. According to recent research, lncRNA plays a crucial role in the regulation of skeletal muscle growth and development [29][30][31]. In the present study, a total of 304 DELs and 1819 DEMs were identified, among which 132 lncRNAs and 1081 mRNAs were found to be down-regulated, while 172 lncRNAs and 738 mRNAs were up-regulated.…”
Section: Discussionmentioning
confidence: 99%